Valorização do bagaço de oliva em biscoitos - Trindade, Pamela Cristiele Oliveira (2022)
Olive pomace is a residue from the processing of olives used for oil extraction. This can be used in several products in the food industry due to its richness in dietary fiber, fatty acids and phenolic compounds. The objective of this work was to elaborate cookies added with olive pomace flour (OF), evaluating the effects of the flour in terms of chemical composition, lipid profile of cookies and sensory aspects. The data showed that FBO has a high concentration of dietary fiber (43.75%), being 37.59% insoluble fiber, lipids (27.70%). Biscuits were prepared in different proportions (0, 10 and 20%) of FBO in place of wheat flour, and were evaluated for chemical, physical and sensory characteristics. The biscuit with the addition of 10% of olive pomace flour, shows the results of dietary fiber, soluble, insoluble (4.29, 0.57, 3.72% respectively), and lipids (22.61%), since for BIS20 dietary fiber, soluble, insoluble (8.52, 0.78, 8.24% respectively), and lipids (23.78%). Regarding the physical characteristics of the cookies with FBO, the luminosity was lower. The data revealed that the incorporation of FBO increases the content of lipids, dietary fiber (mainly insoluble fiber). Sensorially, the terms that most characterized the cookies with FBO were dark color and bitter aftertaste, and salty flavor for BIS20. Biscuits with the addition of olive pomace flour in place of wheat flour showed an increase in dietary fiber content, mineral content, and lipids. The luminosity reduced in the cookies with the addition of olive pomace flour, the texture and the fragility, as well as the cooking loss. Sensorially, the parameters that most characterized the cookies with the addition of olive pomace flour were: salty flavor, aroma of olive oil and dark color. The biscuit with 10% wheat flour replacement is the one with the best sensory characteristics, being the most accepted.